Kinetin Induced Changes in Rutin Content in Knautia sarajevensis (G. Beck) Szabó Shoot Cultures - Karalija, Erna; Kurtagić, Harun; Parić, Adisa (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2014)
Knautia sarajevensis, Dipsacaceae, is an endemic species found at wood margins and meadows only on mountains of Dinaric Alps. Members of this family are widely used in traditional medicine as rich sources of pharmacologically important substances. Since it is well known that flavonoid compounds are one of the main carriers of biological activities of plant extracts, the aim of this study was to investigate cytokinin effects in concentration changes of flavonoid constituents. Four different flavonoid constituents were analysed: quercetin, naringenin, hesperetin and rutin in extracts of K. sarajevenis shoots cultivated on three in vitro treatments (control, 1.0 mg L-1 kinetin and 10.0 mg L-1 kinetin). All extracts were prepared using dried material and 80% methanol HPLC grade. Analysis of rutin indicated that high cytokinin concentrations did induce improvement of rutin content, but these concentrations are still lower than those recorded for control treatment. Further analysis using different types and concentrations of cytokinins are necessary to establish a pattern of cytokinin induced concentration changes in content of these four investigated flavonoids in Knautia sarajevensis.